(untitled) (Anuário Antropológico, 2023)
In recent years, members of many native peoples have enrolled in Brazilian universities after a long struggle and state changes concerning their right to assess specific policies. Previously limited, the indigenous presence on university campuses is drawing attention and posing questions about these students and how the courses they take will be handled in the future by the programs nation-wide covering a vast range of subjects, including anthropology. In terms of general historical and political issues, this process has been likened to the images the dominant society still holds of indigenous peoples, and the institutional structures into which they are admitted, notwithstanding regional variations and specific histories of interethnic contact. Coming from worlds transfigured by colonialism, and deeply aware of it, indigenous scholars seek to “indigenize” university spaces. While condemning the Western-promoted plunder and oppression, they compare it with their own knowledge. On the other hand, they appropriate anthropology’s tools with the political and intellectual purpose of debating and interacting with the surrounding non-indigenous world. Hence, the university becomes a proper setting for their cause, as it includes the public that may be interested in other ways of being in the world.